Evaluation of the efficiency of maintenance and repairs to metallurgical equipment - Biletskyi, V.; Taratuta, K.; Kulik, T. О.; Білецький, В.; Таратута, К.; Кулік, Т. О. (Kryvyi Rih National University, 2025)
Metallurgical enterprises are among the most capital-intensive industries, with high maintenance and repair costs for equipment. The proper management and efficient operation of equipment directly affect product output, safety, and economic performance indicators. The current study aimed to develop key performance indicators for engineering services, emphasising the systematisation of indicators into technical, organisational, and economic groups. This enabled the authors to address the primary challenge of evaluating the efficiency of maintenance and repairs in metallurgical enterprises using the developed key performance indicators. The study analysed and classified thirty-six performance assessment indicators. Using the Delphi expert assessment method and the subsequent step-by-step analysis of weight assessment coefficients via the fuzzy Step-Wise Weight Assessment Ratio Analysis method, the key factors for the operational control of the maintenance and repair efficiency of metallurgical equipment were identified. These factors were categorised into three groups. The first group included five technical indicators; the second, six organisational indicators; and the third, three economic indicators of the efficiency of technical maintenance and repairs of metallurgical equipment. Analysis of the obtained rating of key performance indicators showed that the most significant indicators were complex (generalising) indicators in each group. The key indicators in each group were determined to be: the technical readiness coefficient of equipment; the overall efficiency indicator of equipment; and the cost intensity of technical maintenance and repairs of equipment. Based on the indicator ratings, recommendations were developed for compiling a compliance matrix and priority measures in the event of negative dynamics in each group of indicators. The practical significance of this work lies in providing technical maintenance and repair specialists at metallurgical enterprises with criteria for objectively assessing the current state of equipment management, thereby enabling improvements to be made to the repair system.

Підприємства металургійної промисловості відносяться до найбільш капіталомістких виробництв, з високими витратами на технічне обслуговування та ремонт обладнання. Належне управління та ефективна робота обладнання безпосередньо впливає на випуск продукції, безпеку та економічні показники. Мета поточного дослідження полягала у розробці ключових показників ефективності роботи інжинірингових служб, з акцентом на систематизацію показників по технічним, організаційним та економічним групам. Це дозволило вирішити головне питання оперативної оцінки ефективності технічного обслуговування та ремонтів обладнання металургійних підприємств, з використанням розроблених ключових показників. В роботі проаналізовано та класифіковано тридцять шість показників оцінки ефективності. Використовуючи метод експертних оцінок Дельфі, з подальшим поетапним аналізом коефіцієнтів оцінки ваги за допомогою нечіткого методу поетапного аналізу коефіцієнта оцінки ваги, були встановлені ключові фактори оперативного контролю ефективності технічного обслуговування та ремонтів металургійного обладнання. Зазначені фактори систематизовано у три групи. До першої групи увійшли п’ять технічних показників, до другої групи увійшло шість організаційних показників, до третьої групи – три економічні показники ефективності технічного обслуговування та ремонтів металургійного обладнання. Аналіз отриманого рейтингу ключових показників ефективності показав, що до найбільш значущих показників відносяться комплексні (узагальнюючі) показники у кожній групі. Ключовими показниками у кожні групі визначено: коефіцієнт технічної готовності обладнання, показник загальної ефективність обладнання, витратоємність технічного обслуговування та ремонтів обладнання. На підставі рейтингу показників розроблено рекомендації по складанню матриці відповідності та першочерговим заходам у разі негативної динаміки кожної групи показників. Практична значимість роботи полягає у наданні фахівцям служб технічного обслуговування та ремонтів металургійних підприємств критеріїв об’єктивної оцінки поточний стан управління обладнанням, що дозволяє покращувати систему ремонтів.
Оцінка технічного обслуговування та ремонтів металургійного обладнанняза критеріями ефективності
Keywords: organisational structure; rating; expert assessments; technical readiness coefficient; engineering services; Delphi method; організаційна структура; рейтинг; експертні оцінки; коефіцієнт технічної готовності; інжинірингові служби; метод Дельфі